2013
DOI: 10.1021/jf4022652
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nonnutritional Factors and Antioxidant Activity during Germination of Nonconventional Legumes

Abstract: The present study describes the effects of germination on nonnutritional factors and antioxidant activity in the nonconventional legumes Vigna unguiculata (cowpea), Canavalia ensiformis (jack bean), Lablab purpureus (dolichos), and Stizolobium niveum (mucuna). Protease inhibitors and lectins were detected in raw legumes and were significantly decreased during the germination. Regarding total and individual inositol phosphates (IP5-IP3), important reductions of IP6 and high increases in the rest of inositol pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 35 publications
3
68
1
4
Order By: Relevance
“…Both, DRAC and ABTS methods, showed a similar tendency. Some researchers (Wu et al, 2012;Aguilera et al, 2013;Gharachorloo et al, 2013;Singh et al, 2014;Dueñas et al, 2016) also reported that the germination increased the AoxA of legumes. However, they did not evaluate AoxA in extracts of bound phenolics.…”
Section: Phenolic Content Flavonoid Content and Antioxidant Activitymentioning
confidence: 99%
“…Both, DRAC and ABTS methods, showed a similar tendency. Some researchers (Wu et al, 2012;Aguilera et al, 2013;Gharachorloo et al, 2013;Singh et al, 2014;Dueñas et al, 2016) also reported that the germination increased the AoxA of legumes. However, they did not evaluate AoxA in extracts of bound phenolics.…”
Section: Phenolic Content Flavonoid Content and Antioxidant Activitymentioning
confidence: 99%
“…Germination has been shown to be a very effective process to reduce antinutritional factors and increase bioactive phenolic compounds and antioxidant activities of seeds (Aguilera et al, 2013). Good antioxidant activity, for example, in quinoa seeds, may also be attributed to the presence of vitamin C and tocopherols (Paśko et al, 2009;Tang et al, 2015) which also protects against oxidation of its fatty acids.…”
Section: Fernandezmentioning
confidence: 99%
“…Many studies document the importance of legumes as functional ingredients in some foods, and as therapeutic agents in the diet of healthy vulnerable populations (Campos-Vega et al, 2010; Aguilera et al, 2013;Patrascu et al, 2016). The health promoting ability of vegetables highly depends on the processing, which modulates the level of different bioactive compounds, as well as their activity and bioavailability (Plaza et al, 2003;Rosales-Juárez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that during germination the contents of soluble protein and dietary fiber of legumes increase, as well as digestibility. In addition, germination proved to be effective in increasing the overall antioxidant activity, total phenols, catechins, and proanthocyanidins contents in nonconventional legumes like cowpea, jack bean, dolichos and mucuna (Aguilera et al, 2013). The increase of the bioactive compounds level of the vegetal products can be also obtained through fermentation, by careful selection of different bacterial strains, or by performing metabolic engineering experiments Iyer and Tomar, 2009;Sands et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation